2017
DOI: 10.1042/bsr20160552
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin efficiently promotes cardiac differentiation of mouse embryonic stem cells

Abstract: To investigate the effects of rapamycin on cardiac differentiation, murine embryonic stem cells (ESCs) were induced into cardiomyocytes by 10−4 M ascorbic acid (AA), 20 nM rapamycin alone or 0.01% solvent DMSO. We found that rapamycin alone was insufficient to initiate cardiomyogenesis. Then, the ESCs were treated with AA and rapamycin (20 nM) or AA and DMSO (0.01%) as a control. Compared with control, mouse ESCs (mESCs) treated with rapamycin (20 nM) and AA yielded a significantly higher percentage of cardiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…The mTOR signaling pathway efficiently regulates tissue homeostasis, including the heart. Rapamycin is an mTOR inhibitor and an autophagy inducer 33 . First, several studies reported that inhibition of mTORC1 by knockdown of RAPTOR promotes cardiac differentiation 59 ; however, inhibition of mTORC2 via knockdown of its component RICTOR suppresses cardiac differentiation 60 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The mTOR signaling pathway efficiently regulates tissue homeostasis, including the heart. Rapamycin is an mTOR inhibitor and an autophagy inducer 33 . First, several studies reported that inhibition of mTORC1 by knockdown of RAPTOR promotes cardiac differentiation 59 ; however, inhibition of mTORC2 via knockdown of its component RICTOR suppresses cardiac differentiation 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged rapamycin treatment inhibits the assembly of mTORC2 31 . Rapamycin can continuously promote cardiomyogenesis throughout the process of cardiac induction 33 . Second, the present literature on the autophagy signaling pathway indicates that it plays a crucial role in cell metabolism, proliferation, differentiation, and replicative senescence of (see figure on previous page) Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The β-MHC protein content reflects the differentiation of MSCs into cardiomyocytes to a certain extent, and its gene expression level is one of the important indicators for observing the differentiation of MSCs into mature cardiomyocytes ( 36 ). A previous study found that the upregulation of α-MHC and β-MHC promoted the cardiac differentiation of mouse embryonic stem cells ( 37 ). Furthermore, in a model of LPS-induced sepsis, α-MHC and β-MHC were shown to both be significantly downregulated ( 38 ), which was also identified in the present study.…”
Section: Discussionmentioning
confidence: 99%